A Case of Fetal Ovarian Cyst: Prenatal Detection, Postnatal Diagnostic Approach and Outcome - Eroğlu, Derya; Tekant, Gonca; Akhun, Nilay; Kapucuoğlu, Nilgün (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2017)
ABSTRACT This paper describes the perinatal and postnatal outcome of a case considered to have a fetal ovarian cyst. At 29 weeks of gestation, routine ultrasound examination showed an anechoic cyst 15x16mm in diameter located in the abdomen at the left superolateral side of the bladder. The normal fetal anatomy of other abdominal organs and gender suggested an ovarian cyst as the most likely diagnosis and mesenteric or duplication cyst as differential diagnosis. Ultrasonographic follow-ups documented an increase in size to 40x22mm by 36 weeks of gestation. At postnatal 4 months, ultrasonographic scan showed a left-sided complex ovarian cyst 40x39mm in diameter containing fluid-debris levels and suggesting haemorrhage and/or torsion. At 4.5 months of age laparoscopic exploration demonstrated a normal right ovary and fallopian tube and a left ovary that had undergone torsion and remained a cystic structure. A laparoscopic left salpingo-oophorectomy was performed. Pathological examination demonstrated a microscopic amount of intact ovarian tissue. Fibrosis, dystrophic calcification and multinucleated cells were observed in the cyst wall, suggesting intrauterin torsion of the ovary. Torsion is one of the most serious complications that occur more frequently during fetal life than postnatally and may lead to loss of the gonad.